Produksi tanaman kopi liberika hasil penyambungan intra- dan inter- spesifik pada aplikasi mikoriza dan pupuk anorganik di lahan gambut - Kartika, Elis; Duaja, Made Deviani; Gusniwati, Gusniwati (Jurnal AGRO, 2024)
Increasing the production of Liberica coffee plants in peatlands can be achieved by applying mycorrhiza and using superior plants resulting from intra- and inter-specific grafting. This research aimed to determine the interactions between intra- and inter-specific grafted Liberica coffee plant with combination of mycorrhiza and inorganic fertilizers in peatlands. The experiment was conducted for 6 months on 2-year-old coffee plants used a Split-Plot Design with two treatment factors. The first factor (main plot) consisted of two levels, namely the Liberica coffee plant grafted with Liberica coffee (intra-specific) and Liberica coffee plants grafted with Robusta coffee (inter-specific). The second factor (sub-plot) was the treatment combination of mycorrhiza (Glomus sp-1a and Glomus sp-3c isolate) and inorganic fertilizer, which consisted of six levels: without mycorrhiza + 100% inorganic fertilizer, mycorrhiza + without inorganic fertilizer, mycorrhiza + 25% inorganic fertilizer, mycorrhiza + 50% inorganic fertilizer, mycorrhiza + 75% inorganic fertilizer, and mycorrhiza + 100% inorganic fertilizer according to recommendations. The results showed that there was an interaction between grafted Liberika coffee plants and a combination of mycorrhiza and inorganic fertilizers on the production of Liberika coffee plants. Combining mycorrhiza and 50% inorganic fertilizer was the best combination for producing intra- and inter-specific grafted of Liberica coffee plant in peat land.Peningkatan produksi tanaman kopi Liberika di lahan gambut dapat dilakukan melalui aplikasi mikoriza dan penggunaan tanaman unggul hasil sambung intra- dan inter- spesifik. Penelitian bertujuan untuk mendapatkan interaksi antara tanaman kopi liberika hasil sambung intra- dan inter- spesifik dengan kombinasi mikoriza dan pupuk anorganik di lahan gambut. Percobaan dilakukan selama 6 bulan pada tanaman kopi berumur 2 tahun menggunakan Rancangan Petak Terbagi faktorial dengan dua faktor perlakuan, yaitu faktor pertama (petak utama), perlakuan jenis tanaman kopi hasil penyambungan terdiri dari dua taraf, yaitu tanaman kopi Liberika hasil penyambungan dengan kopi Liberika (intra-spesifik) dan tanaman kopi Liberika hasil penyambungan dengan kopi Robusta (inter-spesifik). Faktor kedua (anak petak) adalah perlakuan kombinasi mikoriza (isolat Glomus sp-1a dan Glomus sp-3c) dan pupuk an-organik yang terdiri atas enam taraf yaitu tanpa mikoriza + 100% pupuk an-organik, mikoriza + tanpa pupuk an-organik, mikoriza + 25% pupuk an-organik, mikoriza + 50% pupuk an-organik, mikoriza + 75% pupuk an-organik serta mikoriza + 100% pupuk an-organik sesuai rekomendasi. Hasil penelitian menunjukkan terdapat interaksi antara jenis tanaman kopi Liberika hasil sambung dengan kombinasi mikoriza dan pupuk anorganik terhadap produksi tanaman kopi Liberika. Kombinasi mikoriza dan 50% pupuk anorganik merupakan kombinasi terbaik untuk produksi tanaman kopi Liberika hasil sambung intra- dan inter-spesifik di lahan gambut.